Applications for future internet : International Summit, AFI 2016, Puebla, Mexico, May 25-28, 2016, Revised selected papers /: International Summit, AFI 2016, Puebla, Mexico, May 25-28, 2016, Revised selected papers. (2017) - Unknown
No abstract available